PEMBELAJARAN SENI PENDEKATAN INTERDISIPLINER DALAM PENGAJARAN: STRATEGI PEMBELAJARAN KOLABORATIF DAN KREATIF - Prasetyo Wati, Kingkin; Hartono; Restu Lanjari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the concept of interdisciplinary art education as a collaborative and creative teaching strategy in the 21st century learning context. The interdisciplinary approach integrates art with other disciplines such as science and technology to create meaningful, holistic, and contextual learning experiences. Using the literature study method, various research findings and theoretical perspectives were analyzed to synthesize effective interdisciplinary strategies in art education. The results show that collaborative learning fosters communication, teamwork, and problem-solving skills, while creative learning encourages innovation and self-expression through exploration of digital media and diverse artistic techniques. Teachers play a crucial role as facilitators in designing learning environments that support cooperation and creativity. The interdisciplinary art learning model not only enhances students’ artistic competence but also strengthens critical thinking, adaptability, and social skills. Thus, the integration of collaborative and creative strategies in interdisciplinary art learning is essential for developing adaptive and innovative learners who are ready to face global challenges.